2018
DOI: 10.1038/s41598-018-24440-w
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated DNA damage responses and increased apoptosis characterize human hematopoietic stem cells exposed to irradiation

Abstract: Failure to precisely repair DNA damage in self-renewing Hematopoietic Stem and early Progenitor Cells (HSPCs) can disrupt normal hematopoiesis and promote leukemogenesis. Although HSPCs are widely considered a target of ionizing radiation (IR)-induced hematopoietic injury, definitive data regarding cell death, DNA repair, and genomic stability in these rare quiescent cells are scarce. We found that irradiated HSPCs, but not lineage-committed progenitors (CPs), undergo rapid ATM-dependent apoptosis, which is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Subclusters comprising cells with the most primitive gene signature showed a lower basal expression of p53 target and DNA repair genes, except for the subcluster enriched for cell cycle genes. Thus, primitive HSCs preserve in short-term culture the previously reported low expression of DDR and DSB repair genes (Beerman et al., 2014, Biechonski et al., 2018) and upregulate these genes when engaging in S/G2. Conceivably, repair of the DNA DSB may thus be delayed in HSC cultured for editing, likely until they engage in DNA replication.…”
Section: Discussionmentioning
confidence: 70%
“…Subclusters comprising cells with the most primitive gene signature showed a lower basal expression of p53 target and DNA repair genes, except for the subcluster enriched for cell cycle genes. Thus, primitive HSCs preserve in short-term culture the previously reported low expression of DDR and DSB repair genes (Beerman et al., 2014, Biechonski et al., 2018) and upregulate these genes when engaging in S/G2. Conceivably, repair of the DNA DSB may thus be delayed in HSC cultured for editing, likely until they engage in DNA replication.…”
Section: Discussionmentioning
confidence: 70%
“…All these approaches have the advantage to achieve a high but transient spike of nuclease expression in the cultured cells, thus limiting its activity to a small window of time and, consequently, alleviating toxicity and off-target activity. Because nuclease-mediated gene editing strictly depends on inducing DNA DSB, the concern was raised whether such breaks, albeit limited to few or even a single genomic site, trigger a DNA damage response (DDR) in the edited HSPC with the potential of inducing adverse effects on their key functional properties, such as long-term hematopoietic repopulation (Ciccia & Elledge, 2010;Milyavsky et al, 2010;Biechonski et al, 2018;Conti & Di Micco, 2018). We and others could overcome at least in part these barriers by extending culture in conditions that drive even the most primitive cells into replication while preserving their engraftment capacity and by tailoring the gene editing machinery to avoid triggering innate immune cellular responses (Genovese et al, 2014;Wang et al, 2015;De Ravin et al, 2016aDever et al, 2016;Schiroli et al, 2017).…”
Section: Precision Genetic Engineering: Targeted Gene Editingmentioning
confidence: 99%
“…Having shown that the pharmacological inhibition of PARP1 expression synergistically enhances the therapeutic effects of the FGFR1 inhibitor PD173074 through a caspase-dependent apoptotic mechanism, against the background that the cleavage/activation of caspases induces DNA fragmentation, cytoskeletal and nucleosomal degradation, protein cross-linking, the formation of apoptotic bodies, and phagocytosis, with subsequent cell death [17,18], we further sought to understand the effect of this synergism on the cancer stem cell-like phenotype of PDAC cells. We investigated the probable effect of olaparib and/or PD173074 on PDAC stem cells.…”
Section: Olaparib Alone or Synergistically With Pd173074 Suppresses Tmentioning
confidence: 99%